Factors Associated with Compliance of Pregnant Women in Consuming Fe Tablets in the Working Area of the Pardamean Health Center, Pematang Siantar City in 2022 - Sitanggang, Tressy; Dalimunthe, Tetty; Purba, Edy Marjuang; Sinaga, Siti Nurmawan; Sinuhaji, Lidya Natalia; Sari, Eka Purnama (Sean Institute, 2022)
The prevalence of anemia in pregnant women in Indonesia from 2013 was 37.1%, increasing to 48.9% in 2018. One of the causes of anemia is non-adherence in taking Fe tablets. The purpose of this study was to determine factors related to adherence. pregnant women consuming Fe tablets in the Working Area of the Pardamean Community Health Center, Pematangsiantar City in 2022. This type of research is an observational analytic study with a cross sectional design. The population in this study were all pregnant women in the Working Area of the Pardamean Public Health Center, Pematangsiantar City in 2022 from May to June, a total of 174 pregnant women. The sample size is 53 people taken using simple random sampling. The statistical test used is the Chi-square test. There is a significant relationship between knowledge (0.001) and behavior of health workers (0.025) with the adherence of pregnant women in consuming Fe Tablets. There is no significant relationship between the role of the family (0.655) and the compliance of pregnant women in consuming Fe tablets. It is recommended that health workers improve their services for pregnant women, especially controlling and following up consumption of Fe tablets in pregnant women.